Implementasi Pendidikan Karakter Berbasis Nilai-nilai Islam Melalui Budaya Sekolah - Kholis, Nur (EDUKASI: Jurnal Pendidikan Islam, 2017)
This study was intended to examine the process of meaning giving of character education values by identifying the process of developing a character-based school culture, both for students, teachers, and other school stakeholders. The research is qualitative in nature with phenomenology design. The research was conducted at Islamic Elementary School (Sekolah Dasar Islam/SDI) Zumrotus Salamah, Tulungagung, East Java. The objects of this study were the values of character education and the character-based school culture. The school principal, the vice principals, the teachers, the students, the school committees, the studentsÃ¢â¬â¢ parents, and the communities around the school were involved as the subjects of the study. The data were collected by administering in-depth interview, documentation and observation techniques. The validity of data was ensured by credibility, transferability, dependability, and confirmability checking techniques. The data were then analyzed in interrelated stages of data display, data reduction, conclusion drawing, and data verification. The results show that the values of character education were elaborated from the trilogy of Islamic doctrines, namely; al-Iman, al-Islam, and al-Ihsan. Finally, the stages of the development of character-based school culture were started from the internalization process of Islamic moral values, the positive change of studentsÃ¢â¬â¢ views and attitudes, and the implementation of character-based traits at schools, at home, and in the daily social activities of students.